Efficacy Evaluation of 10-Hydroxy Chondrofoline and Tafenoquine against Leishmania tropica (HTD7) - Sayyed Ibrahim Shah; Fazli Nasir; Nadia Shamshad Malik; Muhammad Alamzeb; Muhammad Abbas; Inayat Ur Rehman; Fazli Khuda; Yasir Shah; Khang Weh Goh; Alam Zeb; Long Chiau Ming (MDPI AG, 2022)
Leishmaniasis is affirmed as a category one disease (most emerging and unmanageable) by the World Health Organization (WHO), affecting 98 countries with an annual global incidence of ~1.2 million cases. Options for chemotherapeutic treatment are limited due to drug resistance and cytotoxicity. Thus, the search for new chemical compounds is instantly desirable. In this study, we used two compounds, i.e., 10-hydroxy chondrofoline and tafenoquine, for their antileishmanial activity against L. tropica (HTD7). First, the cytotoxicity assay of the test compounds against THP-1 cells was carried out, and these compounds were found safe. Intra-THP-1 amastigote activity (in vitro) was performed, which was then followed by the in vivo activity of 10-hydroxy chondrofoline in the murine cutaneous leishmaniasis (CL) model. A total of three concentrations were used, i.e., 25, 50, and 100 µM, to check the in vitro activity of the test compounds against the amastigotes. 10-hydroxy chondrofoline was found to be the most potent compound in vitro (and thus was selected for in vivo studies) with an LD50 value of 43.80 µM after 48 h incubation, whilst tafenoquine had an LD50 value of 53.57 µM. In vivo activity was conducted by injecting 10-hydroxy chondrofoline in the left hind foot of the infected BALB/c mice, where it caused a statistically significant 58.3% (F = 14.18; p = 0.002) reduction in lesion size (0.70 ± 0.03 mm) when compared with negative control (1.2 ± 0.3 mm).